Cognitive profile of school‐age children and teenagers with hypohidrotic ectodermal dysplasia (HED). Issue 10 (26th August 2014) - Hadj‐Rabia, Smail; Jacob, Stéphane; Dufresne, Hélène; Mashiah, Jacob; Vaivre‐Douret, Laurence; Bodemer, Christine
Abstract : Anhidrotic/hypohidrotic ectodermal dysplasia (HED) is the most common of the ectodermal dysplasias characterized by a triad of absent or reduced sweat, hypodontia and misshapen teeth, and missing or sparse hair. As the central nervous system is primarily ectodermal in origin, it has long been a concern that HED may be associated with developmental delay and/or intellectual disabilities. While published reviews report abnormalities in mental or motor development in 15–25% of HED‐affected patients, there is no report in the literature including a systematic assessment of intellectual abilities in a cohort of patients with this rare disorder. During yearly health care updates, many of our clinic families report attention difficulties in young HED patients without evidence of a significant impact on school performance. In an exploratory study to identify and quantify intellectual abnormalities that may be associated with HED, we performed a psychological examination of 23 HED patients by means of the Wechsler Intelligence Scales, WPPSI‐III, and WISC‐IV. The interpretation of the tests shows no significant impairment in the achievements of the sample group compared with normative values (full scale scores, and index scale scores of the WISC‐IV). At an individual level, the HED‐affected patients were characterised by higher scores on the Verbal Comprehension Index, on Perceptual Reasoning and Working Memory Indices, and lower scores on the Processing Speed Index. As all of the Indices were within normal limits for the study population, in the absence of major mental/motor disabilities these findings support the mainstream education of HED‐affected children. © 2014 Wiley Periodicals, Inc.